Enhancing English Vocabulary through the Moral Values in Roro Jonggrang Folklore - Hidayah, Vita Tri Kurniawati; Irmayani, Irmayani (Journal of English Language and Education, 2025)
Vocabulary development has a critical position in English language learning; however, numerous instructing practices need the connection between culture and ethical integration. Whereas folklore, particularly the story of Roro Jonggrang, offers ethical insights and cultural richness, its potential in vocabulary learning remains underexplored. This consideration points to examining how ethical values from the Indonesian stories of Roro Jonggrang can be coordinated into writing activities to upgrade students' English vocabulary acquisition. Applying qualitative descriptive methods, this study analysed the folklore content utilising content analysis to discover the ethical values and related vocabularies. The findings uncovered eight dominant ethical subjects, like honesty, hard work, humility, responsibility, respect, courage, justice, and wisdom. These topics give important vocabulary when consolidated into reflective writing tasks. The study concludes that writing activities based on the folklore of Roro Jonggrang upgrade vocabulary development and fortify character education, supporting a more relevant and values-driven approach to English learning.